Putusan Ultra Petita Mahkamah Konstitusi - Ach. Rubaie; Nyoman Nurjaya; Moh. Ridwan; Istislam Istislam (The Constitutional Court of the Republic of Indonesia, 2016)
Basic considerations of the Constitutional Court made ultra petita verdict was:(a) philosophical reasons in order to enforce substantive justice and constitutional justice as embodied in the Constitution NRI 1945, (b) theoretical grounds related to the authority of the judge to explore, discover and follow the legal values that live in the community, if the law does not exist or insufficient legal anymore (outdated), and (c) juridical reasons relating to the provision of Article 24 paragraph (1) NRI 1945 Constitution and Article 45 paragraph (1) of Law no. 24 year 2003 on the Constitutional Court, that Court as organizers aim to enforce the judicial justice according to law and the evidence and the judge's conviction. The verdict the Constitutional Court which is ultra petita basically acceptable, all associated to the subject of the request and based on considerations which can be accounted for philosophical (ie, contains the values of justice, morality, ethics, religion, principle, doctrine). The authority to make ultra petita verdict for the Constitutional Court can only be given if there is vagueness of legal norms (vague normen) through the method of interpretation of the law, or if a legal vacuum (rechts-vacuum) through the creation of legal methods (rechtschepping). But considering the legal interpretation and legal formation are highly subjective, hence in order to prevent abuse of power, the Constitutional Court issued a verdict ultra petita, should be limited by the principles of a democratic state of law, the principles of fair trial and impartial, and general principles of good governance.